Math Doubts

Proof $\dfrac{d}{dx}{x^n}$ formula


$\large \dfrac{d}{dx}{x^n}$ $\,=\,$ $\large nx^{n-1}$

$x$ is a variable and it is raised to power of $n$. The varying quantity in a function form is written as $x^{\displaystyle n}$. The derivative of $x^{\displaystyle n}$ with respect to $x$ is used as a formula in differential calculus to differentiate the functions which are in power form.

The differentiation of $x^{\displaystyle n}$ law can be derived in differential calculus by using fundamental method of finding derivative of function with respect to $x$.

$\dfrac{d}{dx}{f{(x)}}$ $\,=\,$ $\large \displaystyle \lim_{h \,\to 0} \normalsize \dfrac{f{(x+h)}-f{(x)}}{h}$

$f{(x)} \,=\, x^{\displaystyle n}$, then $f{(x+h)} \,=\, {(x+h)}^{\displaystyle n}$

Substitute the functions in the formula

Replace the differentiation of a function formula by replacing the values of the functions $f{(x)}$ and $f{(x+h)}$.

$\implies \dfrac{d}{dx}{x^{\displaystyle n}}$ $\,=\,$ $\large \displaystyle \lim_{h \,\to 0} \normalsize \dfrac{{(x+h)}^{\displaystyle n}-x^{\displaystyle n}}{h}$

Simplify the function by taking out common factors

$x^{\displaystyle n}$ is a term in the numerator and the same term can be taken out from the term ${(x+h)}^{\displaystyle n}$.

$\implies \dfrac{d}{dx}{x^{\displaystyle n}}$ $\,=\,$ $\large \displaystyle \lim_{h \,\to 0} \normalsize \dfrac{x^{\displaystyle n}{\Big(1+\dfrac{h}{x}\Big)}^{\displaystyle n}-x^{\displaystyle n}}{h}$

$\implies \dfrac{d}{dx}{x^{\displaystyle n}}$ $\,=\,$ $\large \displaystyle \lim_{h \,\to 0} \normalsize \dfrac{x^{\displaystyle n}\Bigg[{\Big(1+\dfrac{h}{x}\Big)}^{\displaystyle n}-1\Bigg]}{h}$

$\implies \dfrac{d}{dx}{x^{\displaystyle n}}$ $\,=\,$ $\large \displaystyle \lim_{h \,\to 0} \normalsize \dfrac{x^{\displaystyle n}}{h} \times {\Bigg[{\Big(1+\dfrac{h}{x}\Big)}^{\displaystyle n}-1\Bigg]}$

Apply expansion of Binomial Theorem

The term ${\Big(1+\dfrac{h}{x}\Big)}^{\displaystyle n}$ is in the form binomial theorem. So, it can be expanded by applying Binomial theorem.

${(1+x)}^{\displaystyle n}$ $\,=\,$ $1$ $+$ $\dfrac{nx}{1!}$ $+$ $\dfrac{n(n-1)}{2!}x^2$ $+$ $\dfrac{n(n-1)(n-2)}{3!}x^3$ $+$ $\cdots$

In this case, $\dfrac{h}{x}$ is there instead of $x$. So, replace $x$ by $\dfrac{h}{x}$ in the expansion of the binomial theorem.

$\implies \dfrac{d}{dx}{x^{\displaystyle n}}$ $\,=\,$ $\large \displaystyle \lim_{h \,\to 0} \normalsize \dfrac{x^{\displaystyle n}}{h}$ $\times$ $\Bigg[1$ $+$ $\dfrac{n}{1!}{\Big(\dfrac{h}{x}\Big)}$ $+$ $\dfrac{n(n-1)}{2!}{\Big(\dfrac{h}{x}\Big)}^2$ $+$ $\dfrac{n(n-1)(n-2)}{3!}{\Big(\dfrac{h}{x}\Big)}^3$ $+$ $\cdots -1\Bigg]$

Simplify the function to obtain derivative of the function

There is a lot of scope for simplification of this expression and it helps us to get the differentiation of $x^{\displaystyle n}$ easily in the next few steps.

$\implies \dfrac{d}{dx}{x^{\displaystyle n}}$ $\,=\,$ $\large \displaystyle \lim_{h \,\to 0} \normalsize \dfrac{x^{\displaystyle n}}{h}$ $\times$ $\Bigg[\require{cancel} \cancel{1}$ $+$ $\dfrac{n}{1!}{\Big(\dfrac{h}{x}\Big)}$ $+$ $\dfrac{n(n-1)}{2!}{\Big(\dfrac{h}{x}\Big)}^2$ $+$ $\dfrac{n(n-1)(n-2)}{3!}{\Big(\dfrac{h}{x}\Big)}^3$ $+$ $\cdots -\require{cancel} \cancel{1}\Bigg]$

$\implies \dfrac{d}{dx}{x^{\displaystyle n}}$ $\,=\,$ $\large \displaystyle \lim_{h \,\to 0} \normalsize \dfrac{x^{\displaystyle n}}{h}$ $\times$ $\Bigg[\dfrac{n}{1!}{\Big(\dfrac{h}{x}\Big)}$ $+$ $\dfrac{n(n-1)}{2!}{\Big(\dfrac{h}{x}\Big)}^2$ $+$ $\dfrac{n(n-1)(n-2)}{3!}{\Big(\dfrac{h}{x}\Big)}^3$ $+$ $\cdots \Bigg]$

$\implies \dfrac{d}{dx}{x^{\displaystyle n}}$ $\,=\,$ $\large \displaystyle \lim_{h \,\to 0} \normalsize \dfrac{x^{\displaystyle n}}{h} $ $\times$ ${\Big(\dfrac{h}{x}\Big)}\Bigg[\dfrac{n}{1!}$ $+$ $\dfrac{n(n-1)}{2!}{\Big(\dfrac{h}{x}\Big)}$ $+$ $\dfrac{n(n-1)(n-2)}{3!}{\Big(\dfrac{h}{x}\Big)}^2$ $+$ $\cdots \Bigg]$

$\implies \dfrac{d}{dx}{x^{\displaystyle n}}$ $\,=\,$ $\large \displaystyle \lim_{h \,\to 0} \normalsize \dfrac{x^{\displaystyle n} \times h}{h \times x} $ $\times$ $\Bigg[\dfrac{n}{1!}$ $+$ $\dfrac{n(n-1)}{2!}{\Big(\dfrac{h}{x}\Big)}$ $+$ $\dfrac{n(n-1)(n-2)}{3!}{\Big(\dfrac{h}{x}\Big)}^2$ $+$ $\cdots \Bigg]$

$\implies \dfrac{d}{dx}{x^{\displaystyle n}}$ $\,=\,$ $\large \displaystyle \lim_{h \,\to 0} \normalsize \require{cancel} \dfrac{x^{\displaystyle n} \times \cancel{h}}{\cancel{h} \times x} $ $\times$ $\Bigg[\dfrac{n}{1!}$ $+$ $\dfrac{n(n-1)}{2!}{\Big(\dfrac{h}{x}\Big)}$ $+$ $\dfrac{n(n-1)(n-2)}{3!}{\Big(\dfrac{h}{x}\Big)}^2$ $+$ $\cdots \Bigg]$

$\implies \dfrac{d}{dx}{x^{\displaystyle n}}$ $\,=\,$ $\large \displaystyle \lim_{h \,\to 0} \normalsize \dfrac{x^{\displaystyle n}}{x} $ $\times$ $\Bigg[\dfrac{n}{1!}$ $+$ $\dfrac{n(n-1)}{2!}{\Big(\dfrac{h}{x}\Big)}$ $+$ $\dfrac{n(n-1)(n-2)}{3!}{\Big(\dfrac{h}{x}\Big)}^2$ $+$ $\cdots \Bigg]$

Get quotient of $x^{\displaystyle n}$ by $x$ by using quotient rule of exponents.

$\implies \dfrac{d}{dx}{x^{\displaystyle n}}$ $\,=\,$ $\large \displaystyle \lim_{h \,\to 0} \normalsize x^{{\displaystyle n}-1}$ $\times$ $\Bigg[\dfrac{n}{1!}$ $+$ $\dfrac{n(n-1)}{2!}{\Big(\dfrac{h}{x}\Big)}$ $+$ $\dfrac{n(n-1)(n-2)}{3!}{\Big(\dfrac{h}{x}\Big)}^2$ $+$ $\cdots \Bigg]$

Get derivative of the function

Substitute $h$ is equal to zero and simplify the expression to get the derivative of $x$ is raised to the power of $n$ with respect to $x$ in differential calculus.

$\implies \dfrac{d}{dx}{x^{\displaystyle n}}$ $\,=\,$ $x^{{\displaystyle n}-1}$ $\times$ $\Bigg[\dfrac{n}{1!}$ $+$ $\dfrac{n(n-1)}{2!}{\Big(\dfrac{0}{x}\Big)}$ $+$ $\dfrac{n(n-1)(n-2)}{3!}{\Big(\dfrac{0}{x}\Big)}^2$ $+$ $\cdots \Bigg]$

$\implies \dfrac{d}{dx}{x^{\displaystyle n}}$ $\,=\,$ $x^{{\displaystyle n}-1}$ $\times$ $\Big[\dfrac{n}{1}$ $+$ $0$ $+$ $0$ $+$ $\cdots \Big]$

$\implies \dfrac{d}{dx}{x^{\displaystyle n}}$ $\,=\,$ $x^{{\displaystyle n}-1}$ $\times$ $[n]$

$\,\,\, \therefore \,\,\,\,\,\, \dfrac{d}{dx}{x^{\displaystyle n}}$ $\,=\,$ $nx^{{\displaystyle n}-1}$

Math Doubts
Math Doubts is a best place to learn mathematics and from basics to advanced scientific level for students, teachers and researchers. Know more
Follow us on Social Media
Mobile App for Android users Math Doubts Android App
Math Problems

Learn how to solve easy to difficult mathematics problems of all topics in various methods with step by step process and also maths questions for practising.

Learn more